Benefits of hypothermia in neonatal arterial ischemic strokes: A preclinical study. Issue 4 (24th March 2020) - Chevin, Mathilde; Chabrier, Stéphane; Dinomais, Mickaël; Bedell, Barry J.; Sébire, Guillaume
Abstract: Background: There is currently no targeted treatment available for neonatal arterial ischemic strokes (NAIS). Epidemiological studies demonstrated that perinatal infection/inflammation, peripartum hypoxia, and occlusion of the internal carotid tree are the main determinants of NAIS. The well‐established benefit of therapeutic hypothermia (HT) in neonatal encephalopathy due to diffuse hypoxia‐ischemia provides a rationale for the potential use of HT as a neuroprotective strategy in NAIS. Methods: We used a rat model to reproduce the most prevalent human physiopathological scenario of NAIS. The neuroprotective effect of HT was measured by morphometric magnetic resonance imaging, [ 18 F] fluorodeoxyglucose (FDG) metabolic activity by positron emission tomography/computed tomography, and behavioral tests. Results: HT (a) prevented the occurrence of 44% of NAIS, (b) reduced the volume of strokes by 37%, (c) enhanced [ 18 F] FDG metabolic activity within the territory of the occluded carotid artery, and (d) improved motor behavior. Both morphometric and metabolic techniques showed consistently that HT provided a neuroprotective effect located in the motor cortex, hippocampus, and caudate‐putamen. Conclusion: Through combining anatomical, metabolic imaging, and behavioral studies, our study provides evidence of neuroprotective effects of HT in NAIS. These results are potentially translational to human NAIS. Abstract : In this article, we assessed the beneficial effect of therapeutic hypothermia (HT) in a rat model of neonatal arterial ischemic stroke (NAIS). Through combining anatomical, metabolic imaging, and behavioral studies, our study provides new evidence of neuroprotective effects of HT in NAIS.